Analisis Underreaction dan Strategi Momentum pada Perusahaan Sektor Industri Barang Konsumsi yang Tercatat di Bursa Efek Indonesia - Najri, Miftah Khairina; Nurhalis, Nurhalis (Manajemen Inovasi Bisnis dan Strategi, 2025)
This research aims to test the existence of underreaction and momentum strategies in consumer goods industry sector companies listed on the Indonesia Stock Exchange. This testing was carried out for five years, namely the 2018-2022 period. The sample selection technique uses a purposive sampling method. This research uses quantitative methods. The type of data used in this research is secondary data. This test uses monthly closing prices. The type of tool used is the t-test, namely the paired sample t-test. This research is divided into two stages, namely the portfolio formation period and portfolio testing.The results of the research show that there has been an underreaction in the shares of manufacturing companies in the consumer goods and industrial sector by observing significant price and value reversals in several observation periods. The research results also show that there has been a momentum strategy in the shares of manufacturing companies in the goods and consumption industry sector which is indicated by underreaction.Keywords: Underreaction; Price reversa; Momentum strategy; ACAR; CAR; AAR